PROSES PENGAJUAN KLAIM DI ASURANSI TUGU KRESNA - Desita Maharani; Fadilla Fadilla (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Asuransi Tugu KresnaPratama (General Insurance) was founded in 1991 originally named PT Asuransi Ratu Sampoerna and in 1993 the company name changed to PT Asuransi Tugu Kresna Pratama. This research tries to describe how the process of filing motor vehicle claims. AT PT. Tugu Kresna Pratama Insurance. The process of submitting claims for motorized vehicles (1) Immediately notifies / reports to the branch / representative office within three working days, (2) In the event of a claim of losing part of the vehicle, it must be photographed before it is ready for use, either by the branch / representative office or by the repair shop (if necessary), (3) The branch / representative office checks valid claims against the validity of the policy or the conditions of the agreement in the policy, (4) PT tugu kresna carefully analyzes the related claim documents. The decision to accept it is accepted or not, among others, in the event that the claim is not valid, the claim will be immediately rejected (in writing) on the grounds: Not guaranteed the condition of the policy and does not meet the policy requirements Because the loss or accident can be proven to be untrue / engineered (not giving / convey the true facts or fraud).